India is on the way forward to maternal and neonatal tetanus elimination! - Bairwa, Mohan (Landes Bioscience, 2012)
Tetanus is an acute, potentially fatal disease, caused by a bacterium, Clostridium tetani. The disease usually occurs in newborns through infection of the unhealed umbilical stump, particularly when the stump is cut with a non-sterile instrument. NT contributes to 5–7% of neonatal mortality worldwide. Several thousand mothers are also estimated to die annually of maternal tetanus. MNT elimination relies on promotion of maternal tetanus immunization along with safe delivery and avoidance of unsafe abortion and umbilical cord care practices. The Government of India (1983) introduced at least two doses of tetanus toxoid vaccine (TT) to all pregnant women during each pregnancy as a part of its nationwide immunization policy. To date, a total of 15 States including union territories of the India have achieved NT elimination. The remaining Indian States need to strengthen TT coverage to save the lives of neonates as well as mothers from tetanus.